2019
DOI: 10.1021/acs.langmuir.9b01905
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of Thermosensitive Hyperbranched Poly(ionic liquid)s Monolayers

Abstract: We synthesized amphiphilic hyperbranched poly(ionic liquid)s (HBPILs) with asymmetrical peripheral composition consisting of hydrophobic n-octadecylurethane arms and hydrophilic, ionically linked poly(N-isopropylacrylamide) (PNIPAM) macrocations and studied low critical solution temperature (LCST)-induced reorganizations at the air−water interface. We observed that the morphology of HBPIL Langmuir monolayers is controlled by the surface pressure with uniform well-defined disk-like domains formed in a liquid ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 89 publications
1
31
1
Order By: Relevance
“…The values of V Oct /V PNIPAM decreased from 0.44 to 0.15 with increasing PNIPAM content. According to the results of our previous studies based on 13 C NMR, the starting polyester polyol HBP-OH has a degree of branching (DB) of 38.7%, 34 in good agreement with the literature data, which gives DB values of 36−43% for HBP-OH (Boltorn H40), which has a similar chemical structure to the starting HBP-OH in this study but with more terminal hydroxyl groups (64). 56 The determined DB values are valid for both intermediate hyperbranched polysulfonic acids and final HBPs (Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The values of V Oct /V PNIPAM decreased from 0.44 to 0.15 with increasing PNIPAM content. According to the results of our previous studies based on 13 C NMR, the starting polyester polyol HBP-OH has a degree of branching (DB) of 38.7%, 34 in good agreement with the literature data, which gives DB values of 36−43% for HBP-OH (Boltorn H40), which has a similar chemical structure to the starting HBP-OH in this study but with more terminal hydroxyl groups (64). 56 The determined DB values are valid for both intermediate hyperbranched polysulfonic acids and final HBPs (Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The high stability of the circular domains is attributed to the branched architecture and asymmetric chemical composition of S8P8 HBPs. It has been demonstrated that branched copolymers of asymmetric chemical composition with higher content of hydrophobic arms form stable circular domains at the air–water interface, which are preserved to high pressures. , Crowding of multiple hydrophobic arms tethered to a single joint point would favor the formation of highly curved, but stable interfaces, which allow the polymer morphology buried in a circular shape territory, making the transition from spherical to cylindrical morphologies unlikely to happen . For S16P16 HBPs with symmetric peripheral chemical composition, segregation of hydrophobic arms would lead to the formation of a less curved interface, making circular domains more vulnerable to pressure, which causes a morphological transition to a continuous monolayer during compression in the S16P16 monolayers (Figure b). , Above the LCST, the hydrophilic-to-hydrophobic transition of terminal PNIPAM chains promotes rearrangement of the whole HBP molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…hydrophilic PNIPAM macrocations, were synthesized and their assembly behavior at the air-water interface as well as thermoresponsive behavior were investigated in the same group. [100] In addition, thermoresponsive PILs, poly(tetrabutylphosphonium styrenesulfonate)-based microgels copolymerizing with poly[di(ethylene glycol)ethyl ether acrylate] were synthesized and their microdynamic volume phase transition mechanism was studied. [101] The content of hydrophilic PIL moieties plays a significant role in the thermally induced phase transition behavior of microgel systems; that is, the microgels with fewer PIL moieties present a sharp transition behavior and a gel-like state (10%, w/v) in water.…”
Section: Il-based Thermo-responsive Materialsmentioning
confidence: 99%
“…Besides, another novel amphiphilic hyperbranched PILs, which consist of asymmetrical peripheral composition of hydrophobic octadecyl tails and hydrophilic PNIPAM macrocations, were synthesized and their assembly behavior at the air–water interface as well as thermo‐responsive behavior were investigated in the same group. [ 100 ]…”
Section: Il‐based Thermo‐responsive Materialsmentioning
confidence: 99%